Rheumatoid arthritis CD14+ monocytes display metabolic and inflammatory dysfunction, a phenotype that precedes clinical manifestation of disease. Issue 1 (19th January 2021) - McGarry, Trudy; Hanlon, Megan M.; Marzaioli, Viviana; Cunningham, Clare C; Krishna, Vinod; Murray, Kieran; Hurson, Conor; Gallagher, Phil; Nagpal, Sunil; Veale, Douglas J; Fearon, Ursula
Abstract: Introduction: This study investigates the metabolic activity of circulating monocytes and their impact on pro‐inflammatory responses in RA and explores whether this phenotype is already primed for inflammation before clinical manifestations of disease. Methods: Blood was collected and CD14 + monocytes isolated from healthy control donors (HC), individuals at‐risk (IAR) and RA patients. Monocyte frequency in blood and synovial tissue was assessed by flow cytometry. Inflammatory responses and metabolic analysis ± specific inhibitors were quantified by RT‐PCR, Western blot, migration assays, Seahorse‐XFe‐technology, mitotracker assays and transmission electron microscopy. Transcriptomic analysis was performed on HC, IAR and RA synovial tissue. Results: CD14 + monocytes from RA patients are hyper‐inflammatory following stimulation, with significantly higher expression of cytokines/chemokines than those from HC. LPS‐induced RA monocyte migratory capacity is consistent with increased monocyte frequency in RA synovial tissue. RA CD14 + monocytes show enhanced mitochondrial respiration, biogenesis and alterations in mitochondrial morphology. Furthermore, RA monocytes display increased levels of key glycolytic enzymes HIF1α, HK2 and PFKFB3 and demonstrate a reliance on glucose consumption, blockade of which abrogates pro‐inflammatory mediator responses. Blockade of STAT3 activation inhibits this forced glycolytic flux resulting in metabolic reprogramming and resolution of inflammation. Interestingly, this highly activated monocytic phenotype is evident in IAR of developing disease, in addition to an enhanced monocyte gene signature observed in synovial tissue from IAR. Conclusion: RA CD14 + monocytes are metabolically re‐programmed for sustained induction of pro‐inflammatory responses, with STAT3 identified as a molecular regulator of metabolic dysfunction. This phenotype precedes clinical disease onset and may represent a potential pathway for therapeutic targeting early in disease. Abstract : In this study, we demonstrated that rheumatoid arthritis CD14 + monocytes are metabolically re‐programmed for sustained induction of pro‐inflammatory responses, an effect that is mediated by STAT3 signalling and precedes clinical disease onset.